2013
DOI: 10.1007/s13632-013-0103-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Single and Duplex Stage Heat Treatment on the Microstructure and Mechanical Properties of Cast Ti–6Al–4V Alloy

Abstract: The effect of single and duplex stage heat treatment on the microstructure and mechanical properties of cast Ti-6Al-4V alloy was studied. The single stage heat treatment (SSHT) involved solution annealing at 935°C for 10 min followed by water quenching, while the duplex stage heat treatment (DSHT) involved solution annealing at 935°C for 10 min, furnace cooling to 600 and 700°C, followed by isothermal holding for 30 min and subsequent water quenching. The properties characterization was conducted using microst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 11 publications
0
13
1
Order By: Relevance
“…Based on the morphology of α phase, the microstructure of titanium alloys can be classified into equiaxed, lamellar and bi-modal microstructures [24]. The microstructure of Ti-based alloys can be controlled based on their chemical composition, i.e., based on the balance between the α phase stabilizing elements, such as Al, Sn and O, and the forming β phase elements such asV, Mo and Nb [25].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the morphology of α phase, the microstructure of titanium alloys can be classified into equiaxed, lamellar and bi-modal microstructures [24]. The microstructure of Ti-based alloys can be controlled based on their chemical composition, i.e., based on the balance between the α phase stabilizing elements, such as Al, Sn and O, and the forming β phase elements such asV, Mo and Nb [25].…”
Section: Resultsmentioning
confidence: 99%
“…Reda et al’s work on the heat treatment of as-cast Ti-6Al-4V alloy reported significantly inferior impact strengths than those given in other studies on wrought counter parts [4,5]. A typical impact toughness of as-cast material in their work was around 11 J with various α + β heat treatments giving only a limited enhancement in toughness.…”
Section: Introductionmentioning
confidence: 87%
“…There are a number of studies in the literature that investigated the effect of post-processing heat treatments on impact toughness of Ti-6Al-4V alloy produced by conventional ingot/wrought or casting routes [1,4,5,6]. The work done by Meyer et al suggests that heat treatment of mill-annealed Ti-6Al-4V alloy gives a range of impact toughness; however, furnace cooling from the β or α + β phase fields provides the best energy absorption to failure, with values in the range 42–46 J, using U-notch specimens [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the morphology of  phase, the microstructure of titanium alloys can be classified into equiaxed, lamellar and bi-modal microstructures [20]. The microstructure of Ti-based alloys can be Similar to Ti-Al-V and Ti-Al-Nb alloys, the microstructure of TC21 alloy, Fig.…”
Section: Microstructure Investigationmentioning
confidence: 99%